Role making in translational contexts : a qualitative study on the different roles of intercept interpreters/translators in covert communication surveillance - Hohl Zürcher, Franziska; Griebel, Cornelia (John Benjamins Publishing Company, 2024)
This study examines the roles of intercept interpreters/translators (IITs) in covert communication surveillance. Despite their increasing importance in global criminal investigations, their roles remain underexplored in academic research. Utilizing sociological theories of role taking and role making, three distinct IIT roles emerge: “distant service providers,” “deputy police officers,” and “masters of balance.” Each role reflects unique approaches influenced by professional identity and self-defined involvement in police investigations. At the same time, the research highlights the relevance of police trust in IITs. According to our study, role making functions as a negotiation between all stakeholders involved, challenging dichotomous perspectives on norms and expectations. The study advocates for a nuanced approach to IIT roles that integrates forensic-criminalistic considerations into translation practices. It also urges criminal justice authorities to rethink interpreting and translation methods by prioritizing meaningful translations that align with ethical standards and forensic principles.